2021
DOI: 10.1371/journal.pone.0246664
|View full text |Cite
|
Sign up to set email alerts
|

Views and experiences of the female condom in Australia: An exploratory cross-sectional survey of cisgender women

Abstract: Background The female condom is the only female-initiated form of protection against unintended pregnancy and sexually transmissible infections (STIs). However, use of this method in Australia is low. To better understand women’s views and experiences of the female condom, we conducted an interventional cross-sectional study. Methods Cisgender women ≥16 years, heterosexually active and living in New South Wales were recruited through social media advertisements and email invitations to clients of a family pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Studies done elsewhere in the world reveal similar findings. In Australia, for example, condoms were found beneficial in preventing pregnancies and STIs, but it was revealed that health education ought to be channeled to female condom use [45]. Studies done in Brazil revealed the increased prevalence of risky sexual behaviour and teenage pregnancy to be due to a low level of knowledge on contraception methods, a lack of knowledge regarding longacting reversible contraceptives, and poor attitudes towards contraception [46 -48].…”
Section: Discussionmentioning
confidence: 99%
“…Studies done elsewhere in the world reveal similar findings. In Australia, for example, condoms were found beneficial in preventing pregnancies and STIs, but it was revealed that health education ought to be channeled to female condom use [45]. Studies done in Brazil revealed the increased prevalence of risky sexual behaviour and teenage pregnancy to be due to a low level of knowledge on contraception methods, a lack of knowledge regarding longacting reversible contraceptives, and poor attitudes towards contraception [46 -48].…”
Section: Discussionmentioning
confidence: 99%